The Economic Changes In The Global Economy During The Covid-19 Pandemic - Ireneusz MICIUŁA; Katarzyna KAZOJĆ; Dominik KABUS (Communications of International Proceedings, 2022)
The aim of the article is to show the changes among global economic indicators as a result of the global Covid-19 pandemic. The analysis of economic changes allows the discovery of trends in world economies and the creation of practical recommendations as to the principles of crisis management during global perturbations. The subject of the work is current and allows you to draw conclusions for the optimal management of the economies of countries during various crises with the use of available methods and information technologies.
Keywords: Business; Socio-Economic System; Economic Development Policy; Economy; Entrepreneurship.